A synthesis of Sphagnum litterbag experiments: initial leaching losses bias decomposition rate estimates - H. Teickner; H. Teickner; E. Pebesma; K.-H. Knorr (Biogeosciences)
Our knowledge of the magnitude and controls of Sphagnum decomposition rates is derived to a large extent from litterbag experiments that do not explicitly consider initial leaching losses. Previous research on vascular plants suggests that decomposition rate (k0) estimates from litterbag experiments are biased when initial leaching losses (l0) are ignored. In contrast, the magnitude and variability of l0 for Sphagnum litterbag experiments are not well known, and it is therefore also not known how much Sphagnum k0 estimates are biased. As Sphagnum is the main peat-forming species in many northern peatlands, and biases in k0 estimates can propagate and amplify in long-term peatland models, minimizing such bias is necessary for accurate predictions of peat accumulation.